FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA SEKTOR INFRASTRUKTUR - SUKAMPO, CAROLINE; HENDRA, HENDRA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
This study aims to analyze and determine the influence of Liquidity, Leverage, Sales Growth, Firm Age, and Firm Size on Profitability. The object of research used is the infrastructure sector company listed on the Indonesia Stock Exchange from 2016-2022. This study uses secondary data and the sample used infrastructure companies listed on the Indonesia Stock Exchange from 2016-2022. The research method used is purposive sampling and there are 20 companies that meet the research criteria out of a total of 42 companies, resulting in a total sample of 120 samples. The research analysis is done using multiple linear regression method with panel data. The results showed that Liquidity, Sales Growth, and Firm Size have a significant positive effect on profitability, while Firm Age, and Leverage have a significant negative effect on profitability. High liquidity increases the company's ability to meet unexpected losses or cash needs without having to sell investments prematurely. Increasing sales growth indicates that the company performs well, therefore it can generate high revenue, which in turn leads to higher profitability, which in turn will ultimately make the company considered highly profitable. Then, a large company allows the company to achieve better economies of scale, access better markets, and increase investor and customer confidence. So that in the end it can increase the company's profitability.